Assessing the Global Burden of Ischemic Heart Disease: Part 2: Analytic Methods and Estimates of the Global Epidemiology of Ischemic Heart Disease in 2010 - Mohammad H. Forouzanfar; Andrew E. Moran; Abraham D Flaxman; Gregory A. Roth; George A. Mensah; Majid Ezzati; Mohsen Naghavi; Christopher J L Murray (2012)
Global Heart is the official and primary publication of the World Heart Federation, offering a platform for the dissemination of knowledge on research, developments, trends, solutions and public health programmes in the area of cardiovascular disease. Global Heart welcomes research results, points of view and educational material on the prevention, treatment and control of cardiovascular disease with a special focus on low and middle-income countries which are facing the brunt of epidemiological transition.Global Heart strongly encourages authors to adhere to CONSORT, STROBE, STARD, and PRISMA guidelines for reporting of clinical trials, observational studies, diagnostic test accuracy papers, and systematic reviews or meta-analyses. Authors are required for submission to download and complete the appropriate Equator Network checklist: http://www.equator-network.org/.